PENGARUH AKUNTABILITAS, KARAKTERISTIK PERSONAL AUDITOR, DAN SKEPTISME PROFESIONAL PADA KUALITAS AUDIT - Dewi, Ni Komang Ayu Puspita; Suputra, I Dewa Gede Dharma (E-Jurnal Akuntansi; Vol 17 No 3 (2016), 2016)
The purpose of this study was to obtain empirical evidence of the influence of accountability, personal characteristics of the auditor, and professional skepticism on audit quality. The population contained in KAP in Bali Province. Respondents in this study was auditor at KAP. The population in this study is the firm that is in the province of Bali. The method of determining the sample selected was non-probability sampling with saturated sampling technique. The study used survey methods (survey method), by distributing questionnaires to the respondents. Respondents in this study was an auditor at KAP in Bali Province. This questionnaire using Likert scale 4 score. Mechanical analysis using multiple linier regression analysis. Based on the analysis found that the disclosure of accountability, personal characteristics of the auditor, and professional skepticism significant positive effect on audit quality.
Keywords: Accountability, Personal Characteristics Auditor, Professional Skepticism, Quality Audit